Uji kadar Air, Cemaran logam dan Jumlah Kalsium Oksalat Tepung Porang (Amorphophallus oncophyllus) - Dian Ratna Rianti; Octariana Sofyan; Setiawan Dwi Anggoro; Rafli Adnan Riza; Ragil Puspita Megaranu; Melati Permata Hati (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
Porang (Amorphophallus oncophyllus) is a widely cultivated plant. The processing of porang tubers into raw materials in the form of flour is carried out to increase the sale value. The resulting flour must be considered related to water content, metal contamination, and the amount of calcium oxalate which can affect quality. Moisture content can affect the stability and shelf life of the material. Metal contamination and the amount of calcium oxalate are related to the safety of the material for consumption. This study aims to determine the processing of porang tubers into porang flour on the value of water content, metal contamination and the amount of calcium oxalate. Porang tubers are processed by adding NaCl, citric acid, and continued with fermentation using lactic acid bacteria (LAB). Porang flour obtained was subjected to tests including water content, Pb metal contamination, and the amount of calcium oxalate. The results of testing for water content, metal contamination and the amount of calcium oxalate obtained were below the standard limit values for SNI 7939-2020. The results of the processing of porang flour produced values for water content, metal contamination and the amount of calcium oxalate that met the requirements.